Investigation of machining characteristics of LBMed Al/Al2O3, Al/SiC and Al/ZrO2 MMCs - Sharma, Vikas (My University, 2017)
In the past time, MMCs materials were famous by the name of steel-wire reinforced copper. This MMC was the material named as continuous-fiber reinforced composites. In 1960s, the aerospace industry was demanding for the high performance material having low weight and high thermal coefficient. The development of MMCs material in the late 1980s provided new revolution to the aviation industry. With the advancement in the properties of these materials, the applications started towards the development of critical space system. Metal matrix composite is a distinct material as it has valuable physical properties as compared to other materials. MMCs gain the properties of two different materials by various fabrication processes. It composed of two or more distinct phases namely matrix phase and reinforcing phase. This material has many applications due to its different properties such as adjustable coefficient of thermal, high strength, high temperature stability expansion, high stiffness, low density, high electrical and thermal conductivity, corrosion resistance, improved wear resistance etc. The fabrication process of MMCs materials depends on the application in particular field. The main focus is provided on the uniform distribution of reinforcement components (reinforced particles) during the manufacturing process of MMCs material. Aluminium alloy (5052) MMCs is made by stir casting method which may replace some of the old industrial applicable materials. The machining of these MMCs materials by the traditional machining methods is a typical process due to some issues related to tool wear and surface roughness. Now days the non-conventional machining process is being used for machining of these metal matrix composites materials. An attempt has been made for machining of these MMCs material by various non-conventional process such as laser beam machining (LBM), electric discharge machining (EDM), abrasive water jet machining (AWJ), ultrasonic machining (USM). These non conventional machining techniques also have some disadvantages such as cutting cost, cutting speed, unable to cut typical geometries, low material removal rate, surface finish, physical constraints with respect to workpiece geometry etc. To overcome these difficulties, the present research work is carried out using laser beam machining (LBM) for machining of MMCs material and for cutting of complicated geometries. This research work investigated the laser beam machining (LBM) characteristics of MMCs consisting of aluminium alloy Al5052 as base material. This study would provide benefits to manufacturing engineers to increase the quality of edge cutting and decrease the cost of laser machining operations. The emphasis has been devoted on laser curve cutting by using different arc radius and variation of percentage reinforced particles to analyse the effect on different output parameters. The various samples of Al5052/Al2O3, Al5052/SiC and Al5052/ZrO2 metal matrix composite (MMC) material were fabricated using stir casting set-up. The various objectives have been completed using CO2 laser setup for determining the machining characteristics on MMCs material. The experimental run layout is designed with the help of Box-Behnken design approach. To investigate the effect on output responses, various process parameters were selected such as cutting speed, laser power, nozzle stand-off distance, nozzle diameter, gas pressure, percentage reinforced particles, arc radius, type of gas, laser frequency, and material thickness. The various MMCs such as Al/SiC, Al/Al2O3 and Al/ZrO2 selected as work material. The optimized model has been developed for various output responses such as dross height, kerf taper, edge surface roughness, kerf deviation, striations, heat affected zone width, material removal rate, energy losses using response surface methodology (RSM). These responses have been optimized using multi-response optimization through desirability functional approach. The analysis of variance has been utilized to evaluate the significance of predicted RSM model. The validity and adequacy of predicted model has been confirmed using experimentation work based on response model. The optimized parameter settings have been identified for various output quality characteristics. The finite element method was applied for determining the effect of curved cut geometry for induced stress and temperature analysis. The transient thermal model and static structural model is applied to determine the results of temperature and stress conditions. The value of heat flux has been found using variable temperature conditions. The formation of new compound Al4C3 has been examined on laser machined surface using X-ray diffraction technique. The laser cutting speed, percentage reinforced particles and arc radius has been found significant factors for the laser cutting process on various quality characteristics. The morphological and metallurgical changes have been determined using SEM, EDS, optical microscope and XRD technique. The heat affected zone, recast layer, crack formation and dross height is characterized using scanning electron microscope.
Keywords: Zro2, Sic, LBMed, recast, cracks; Composite material; laser machining